Pre-vaccination distribution of human papillomavirus (HPV) genotypes in women with cervical intraepithelial neoplasia grade 3 (CIN 3) lesions in Slovenia - Kovanda, Anja (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2009)
Background: High-risk human papillomaviruses (HPV) are the main etiological factor of cervical cancer. Cervical intraepithelial neoplasia grade 3 (CIN 3) is the latest pre-invasive stage of cervical cancer, with an approximately 20% progression rate to invasive cervical carcinoma. Objective: To establish the pre-vaccination distribution of HPV genotypes in Slovenian women with CIN 3 lesions, in order to assess the potential benefit of prophylactic HPV vaccination in Slovenia, and to provide baseline data for monitoring the potential replacement of HPV genotypes under selective pressure of HPV vaccines. Methods and results: A total of 261 cervical swabs collected from women with histologically confirmed CIN 3 lesions were analyzed using four genotyping methods: the Abbott RealTime High Risk HPV Assay, the Innogenetics INNO-LiPA HPV Genotyping Extra Test, and the in-house PGMY09/11, and CPI/CPIIg polymerase chain reaction (PCR) and sequencing. Of 261 samples, 253 (96.9%) were HPV positive. The most common HPV genotype in CIN 3 lesions in the Slovenian samples was HPV-16 (59.0%), followed by HPV-31 (7.5%), HPV-33 (7.1%), HPV-58 (5.0%), and HPV-51 (4.0%). The presence of more than one HPV genotype was detected in 49/253 (19.4%) samples. Together, HPV-16 and HPV- 18 accounted for 67.4% of CIN 3 lesions in this Slovenian population. Conclusion:The high proportion of CIN 3 lesions caused by HPV-16 and HPV-18 should further support the recent decision to include the prophylactic vaccination against HPV in the national vaccination program in Slovenia.
Keywords: Adult; Aged; Aged, 80 And Over; Cervical Intraepithelial Neoplasia; diagnostika; Genotip; genotipizacija; Genotype; ginekologija; Maternica, vrat, intraepitelijska neoplazija; maternični vrat; Odrasli; papiloma virusi; Slovenia; Slovenija; Starost 80 in več; Starostniki; Virology